2011
DOI: 10.1093/chemse/bjr025
|View full text |Cite
|
Sign up to set email alerts
|

Otter Scent Signals Age, Sex, and Reproductive Status

Abstract: Scent is used across taxa to communicate information about signaler identity. Eurasian otters Lutra lutra are mainly solitary and thought to use scent as their primary means of communication. Little is known, however, about what information otters communicate through scent or what social function this performs. Headspace solid-phase microextraction and gas chromatography-mass spectrometry were used to sample and analyze volatile organic compounds from anal scent gland secretion from 158 otters of differing sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 39 publications
4
51
0
Order By: Relevance
“…The suggestion of a seasonal change between those animals which died in colder vs. warmer months indicates that the animals may be using their glands for chemical communication during reproduction. This is similar to the behavior (Gorman et al 1978) and variation in the chemical composition of anal gland secretions (Kean et al 2011) observed in the river otter. However, the otter deposits its secretions on land, while the manatee would deposit into an aqueous environment.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The suggestion of a seasonal change between those animals which died in colder vs. warmer months indicates that the animals may be using their glands for chemical communication during reproduction. This is similar to the behavior (Gorman et al 1978) and variation in the chemical composition of anal gland secretions (Kean et al 2011) observed in the river otter. However, the otter deposits its secretions on land, while the manatee would deposit into an aqueous environment.…”
Section: Discussionsupporting
confidence: 84%
“…Anal glands have never been associated with a function other than those related to chemosensation. Animals that use anal glands for reproductive communication typically produce varying amounts and types of secretions in relation to their reproductive cyclicity (Gorman et al 1978, Kean et al 2011).…”
mentioning
confidence: 99%
“…With regard to the bacterial patterns, these findings replicate and extend previous results obtained using a DNA fingerprint method 23 . Sex-specific odorants or odour mosaics are widespread across animal taxa 10, 4447 and have been detected in several species of mongooses 9, 48 . In meerkats, these sex differences in signal production or expression are congruent with the meerkats’ differential behavioural responses to the presentation of anal-pouch mixtures from conspecific females and males (Leclaire, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that the chemical composition of body odors changes in an age-dependent manner in a variety of non-human animals, such as mouse [19], [20], [21], black-tailed deer [22], rabbit [23], otter [24], and owl monkey [25].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Osada and colleagues [20] demonstrated that mice can discriminate between adult and old-age conspecifics based on body odor alone and that this effect was mediated by differences in the quality, rather than the intensity, of the body odors. Together, this evidence suggests that several non-human animal species have the ability to process the age-dependent signals in body odor, and a few studies have even demonstrated that human participants are able to discriminate between animals of different ages based on their body odors alone [23], [24]. Nevertheless, whether humans, like mice, have the ability to infer the age of conspecifics based on body odors alone remains unanswered.…”
Section: Introductionmentioning
confidence: 99%